Prevention of trichinellosis on fur farms - A. V. Uspensky; L. A. Napisanova (Российский паразитологический журнал)
The purpose of the research is analysing a complex of veterinary and sanitary preventive measures against trichinellosis on fur farms.Materials and methods. The system of measures against trichinellosis is based on creating conditions on fur farms that are aimed at prevention of the invasion, and includes occasional immunological screening of animals, examination of dead animals for trichinellosis and observation of veterinary, sanitary and zootechnical requirements for animal management.Results and discussion. The sero-epizootic monitoring methods of elderly animals implemented on farms based on ELISA and Capillary Ring Precipitin Test allows us to identify infected animals and exclude them from the technology system of maintenance and breeding. The general situation of trichinellosis can be determined by results of studies by a compression or enzyme methods of animal carcasses during the period of mass slaughter for fur.